Sustainable rural and urban ecosystems: Design, implementation and operation : Manual for practice and study - Glücklich, Detlef; Geller, Gunther (Springer Berlin Heidelberg, 2012)
These days human beings have a profound influence on aspects of the planetary ecosystem, e.g. on climate change and biodiversity, to name only two.  This manual is intended to help practitioners, who are dealing with human-based rural and urban settlement-ecosystems, in the key steps towards their realization (design, implementation, and operation) and helpful for all, who are concerned about ensuring their practical sustainability. The ecosystem-approach is holistic and integrative, encompassing various disciplines like architecture, landscape architecture, environmental engineering, social sciences, life sciences, ecology, and management. It also considers issues such as energy-savings, ecological cycles, reuse, natural resources, socio-cultural background, real participation, and holistic quality management. Thus it not only explains the general concept, the steps of realization and the respective involved stakeholders, but also gives hints and tools for practitioners. The information, recommendations and tools are directed to the following target groups, among others: • Local planning authorities (giving hints for the procedure and the involved stakeholders) • Designers (holistic approach, procedures, tools) • Regulatory bodies, licensing and financing authorities (requirements for approach and procedures) • Construction and implementing firms and institutions (recommendations, tools) • Operating bodies (hints for operation, tools) The experiences are based on a joint German-Ghanaian program at Valley View University, the biggest private university in Ghana, intended to help realize the vision of a truly holistic ecological university. It was financed originally by the German Ministry of Education and Research and recently by the German Ministry for the Environment in the frame of the Climate Change Initiative of the Federal Government of Germany.